Strategy for Writing Research Results Articles in Order to Penetrate Reputable Journals: A Case Study of PNBP Research FKIP Mataram University in 2020 - Nuriadi Nuriadi; Ni Nyoman Sri Putu Verawati; Saharudin Saharudin; Ilham Syahrul Jiwandono (Budapest International Research and Critics University, 2022)
Research as one of the pillars of Tridharma apart from education and community service, has a central role in the effort to realize the vision of FKIP Mataram University. But the problem is, there are still many FKIP lecturers at the University of Mataram who have not published their research results in 2020. Strategies and tricks are needed so that lecturers can publish their research results. The method in this study uses a qualitative method with the type of case study. The research flow goes through the stages of preparation, implementation and data analysis. The research location is at FKIP, University of Mataram. Data sources are primary and secondary data sources. Primary data sources are lecturers at the Faculty of Teacher Training and Education (FKIP) who submit 2020 PNBP research spread across four majors, namely the Department of Education, Department of Mathematics and Natural Sciences, Department of Language and Literature and Department of Social Studies. While secondary data sources are reports and articles on the results of PNBP research in 2020. Data collection techniques use interviews and documentation. Data analysis uses data collection, data condensation, data display and drawing conclusions. Test the validity of the data using triangulation methods and references. The mandatory output in this research is scientific publication in national journals or proceedings. The additional output is an academic text that can be used as a policy at FKIP Mataram University. The results of the study show that there are still some obstacles faced by lecturers in publishing research results, namely: the ability to write and find ideas, the ability to use technology, foreign language skills, lack of cooperation, literature review.